Use of Accounting Information in a Multi-Project Organization – The Role of Temporality and Permanency - Linderoth, Henrik CJ (Asian Accounting and Auditing Advancement, 2012)
Studies on the use of accounting information have with a few exceptions not highlighted the role of the organizational form for the use of accounting information. In studies of management and organization, the multi-project organization (MPO) and its managerial implications have received increased attention during the last decade, but its implications for the use of accounting information have not been studied in any depth. Accordingly is the aim of the paper to explore how the MPO’s dimensions of temporality and permanency shape the use of accounting information in a multi-project organization. The aim will be pursued by a case study of a Swedish building and construction company. Based on the empirical data it is concluded that the temporality of operations implies that higher-level managers need more encompassing non-financial information in order to judge accounting information and by that they also get more involved in operations. At the same time, operation managers, i.e. the site manager in a project, have a central role when accounting information for higher-level managers is generated. Finally is it suggested that multi-project organizations need to be categorized in future studies of the use of accounting information in multi-project organizations?